A note on Finnish property criminality - Matti Virén (Bank of Finland, 1990)
This note presents new evidence on Finnish property criminality. The analysis is based on Earlichls (1973) model; the empirical an~lysis makes use af annual Finnish data for the period 1951 - 1986. The estimation results strongly support the notion that both the appreh~nsion rate and the severity of punishment have a strong deterrence effect on larcenies and robberies.
URN:NBN:fi:bof-201807311804
Keywords: 330